Religious anxiety and misunderstanging beliefs: islam in elizabethan britain up to 1603 - Chenafi, Bouchera; Seddiki, Mohamed Cherif (University of Ammar Theledji -Laghouat, 2020)
The relations between Islam and the western world date back to the depths of the history when the two worlds did not know anything about each other, a relationship that was crowned with success and cooperation on many levels. The aim of the work at hand is to unveil the truth of this relationship in order to show what Islam truly is unlike what is promoted to on media and its relations to terrorism. Lately, there has been a massive war raised against Islam in the west what caused a religious anxiety against Islam and Muslims around the world. By going back to the history of Islam and Britain, can the nations of the present day learn from the past or is it just stories and tales? In order to achieve the underlined objectives, an analytical descriptive approach is used so as to demonstrate astonishing details about the history of England and the Islamic world. First it provides an introductory overview about the reign of Elizabeth I (1558 – 1603) which aims at discerning the nature of the relationship between England and the Islamic world on many levels: Political, economic, and military. Second, this research explores the reasons behind the promotion and the widespread of anti-Islam sentiment that caused a religious anxiety throughout the analysis of the anti-Islamic discourses and the writings that deem Islam to be the religion of violence. thus, This study reveals that the relations between England and the Islamic world during the reign of Elizabeth I were established in cordial conditions that led to the emergence of one of the most remarkable alliances of the British history. And This fact was blurred rather than being highlighted in the records of the western history the thing that led to the current misrepresentation of Islam and therefore the dilemma of religious anxiety in the western society